2017
DOI: 10.12932/ap-160217-0024
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among Caregivers and Growth in Children with Parent-reported Food Allergy

Abstract: Parent-reported food allergy could put caregivers under high stress, but the OFC test could reduce stress among anxious, over-parenting caregivers. Parent-reported food allergy had no impact on a child's growth in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results of the APPEAL study are in line with previous studies that documented the negative impact of PA on HRQL [ 19 ], and indicate that findings from research conducted in other countries—including the UK [ 12 , 20 ], US [ 13 , 21 , 22 ], Thailand [ 23 ], Denmark [ 24 ], and Canada [ 22 , 25 ]—also apply to individuals affected by PA in France. In addition, these results, particularly from APPEAL-2, support the previous finding that there is a large variation in the impact of PA [ 13 ], with many individuals coping well while some report a significant psychosocial burden.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the APPEAL study are in line with previous studies that documented the negative impact of PA on HRQL [ 19 ], and indicate that findings from research conducted in other countries—including the UK [ 12 , 20 ], US [ 13 , 21 , 22 ], Thailand [ 23 ], Denmark [ 24 ], and Canada [ 22 , 25 ]—also apply to individuals affected by PA in France. In addition, these results, particularly from APPEAL-2, support the previous finding that there is a large variation in the impact of PA [ 13 ], with many individuals coping well while some report a significant psychosocial burden.…”
Section: Discussionsupporting
confidence: 86%
“…Therapeutic elimination diets have been shown to produce symptomatic emission and are the primary treatment for food allergies [ 13 , 28 ], however, several studies have stated the effect of decreasing children's nutritional status [ 29 , 30 ]. So the management of the elimination diet requires knowledge through proper and careful education in its implementation [ 31 ], and periodic evaluation of the nutritional status of children with food allergies is required [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, therefore, makes it difficult to assess the true dimension of the food allergy problem, whether for comparative purposes, for knowledge, or for planning government actions. Several previous studies [ 2 , 3 ] have shown that there is an inconsistency between family perception and expert assessment of food allergies, which may lead either to under-diagnoses or excessive diagnoses and unnecessary dietary restrictions [ 4 ]. Moreover, besides possible genetic influences, other factors such as specific eating and cultural habits of each assessed region, different perceptions of health problems by studied populations, and even the health and illness process itself may underlie divergences in the prevalence of food allergies among different urban centers, namely between larger and smaller cities.…”
Section: Introductionmentioning
confidence: 99%
“…This, therefore, makes it difficult to assess the true dimension of the food allergy problem, whether for comparative purposes, for knowledge, or for planning government actions. Several previous studies [2,3] have shown that there is an inconsistency between family perception and expert assessment of food allergies, which may lead either to under-diagnoses or excessive diagnoses and unnecessary dietary restrictions [4]. Moreover, besides possible genetic influences, other factors such as specific…”
Section: Introductionmentioning
confidence: 99%